Percentage of Male Peranakan Ettawa Goat Non-Carcass Given Different Local Feed - S. Suparman (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2018)
This study aims to see the percentage of non-carcasses of male Peranakan Ettawa goats as many as six heads fed different local feed, analysis study was using analysis of variance using Completely Randomized Design (CRD) and the parameters measured in this study were non-carcass percentage including skin, head, legs, liver, spleen, lung, trachea, heart, testis, omental fat, and tail. The average of noncore rate obtained during P1 (100% mulberry) research was 70,58%, P2 (50% mulberry and 50% Gamal) was 72,25, and P3 (100% Gamal) was 62,305. Based on the analysis of variance, the result showed that different local feeding at 100% level in this study also had no significant effect (P .05) on the increase of non-carcass weight of male Peranakan Ettawa goat.